Two new species of Xenocona Gilmour, 1960 (Cerambycidae, Lamiinae) with biogeographical notes - Nascimento, Francisco Eriberto De L.; Botero, Juan Pablo; Ávila-Jimenez, Angelo Julián; V, Carolina Cristal Goycolea (Zootaxa, 2025)
Two new species are described for the genus Xenocona Gilmour, 1960 (Cerambycidae, Lamiinae, Acanthocinini): Xenocona plagiata sp. nov. from Colombia and X. queros sp. nov. from Peru. Additionally, photographs and distribution maps are provided. The distribution pattern of species was analyzed in relation to the following environmental variables: humidity (%); average annual temperature (°F); altitude (masl); and average annual precipitation. In general, we observed that the temperature and altitude variables are intrinsically related to the distribution. We also observed that the distribution follows that of conifers trees, which are possibly the host plants of Xenocona species.